Surviving the Trenches: The Personal Impact of the Job on Probation Officers - Lewis, Kirsten R. (American journal of criminal justice, 2013)
The purpose of this study was to assess traumatic stress and burnout in probation officers who work with criminal offenders. Adult probation officers from five departments in three states (Arizona, California, and Texas) participated in this study ( N = 309). Officers completed several survey instruments including the Impact of Events Scale-Revised (Weiss & Marmar, 1997 ), the Compassion Satisfaction/Fatigue Self-Test for Helpers (Steed & Bicknell, 2001 ), and the Probation Personal Impact Scale (PPI). The results indicated officers who reported violent and sexual recidivism on their caseloads, offender suicide, and threats and/or assaults in the line of duty scored significantly higher on measures of traumatic stress and burnout than officers who did not experience these caseload events. Assessments, education, training, and stress management programs are discussed as options to mitigate negative impacts, enhance the resiliency of officers, and improve the quality of evidence-based practices.